2019
DOI: 10.31940/soshum.v9i3.1373
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Students' Self-Compassion Level

Abstract: ___________________________________________________________________It is believed that self-compassion is an essential component for any human being to survive in their environment. Self-compassion is the ability to entertain and care for oneself in suffering, failure, and imperfection rather than taking part in self-criticism. This research attempts to find out the level of self-compassion in vocational higher education students and to explore the differences in terms of self-compassion between male and femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Muris et al (2016) reported nonsignificant gender differences in selfcompassion. Ariyani and Hadiani (2019) illustrates that females are dominant in practicing self-kindness rather than common humanity and mindfulness. Female students seem to have more ability to comprehend and accept themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Muris et al (2016) reported nonsignificant gender differences in selfcompassion. Ariyani and Hadiani (2019) illustrates that females are dominant in practicing self-kindness rather than common humanity and mindfulness. Female students seem to have more ability to comprehend and accept themselves.…”
Section: Discussionmentioning
confidence: 99%